ANTIBACTERIAL EFFECTS OF SINGLE AND COMBINED CRUDE EXTRACTS OF SYNADENIUM GLAUCESCENS AND COMMIPHORA SWYNNERTONII - OCHOLLAH, Mary G.; MSENGWA, Zaituni S.; MABIKI, Faith P.; KUSILUKA, Lughano J.M.; MDEGELA, Robinson H.; OLSEN, John E. (African Journal of Infectious Diseases (AJID), 2022)
Background: Synadenium glaucescens and Commiphora swynnertonii are among the reported plants used traditionally for treatment of bacterial infections. This study reports antibacterial effects of single and combined extracts from leaves, stem and root barks of Commiphora swynnertonii and Synadenium glaucescens. Materials and Methods: Plants were collected from Manyara and Njombe regions in Tanzania. Extraction was done using dichloromethane and methanol. The extracts were assessed for antibacterial activity against Gram-positive bacteria (Staphylococcus aureus and Enterococcus faecalis) and Gram-negative bacteria (Escherichia coli, Klebsiella pneumonia and Pseudomonas aeruginosa). Minimum Inhibitory Concentrations (MIC) was determined by broth microdilution, while Fractional Inhibitory Concentration (FIC) indices were calculated from MIC values of combined extracts to determine combination effects. Results: Strong antibacterial activities were demonstrated by all extracts of S. glaucescens (MIC 0.011-0.375mg/mL) against Gram-positive bacteria and methanol extracts of C. swynnertonii (MIC 0.047-0.375mg/mL). Synergistic effect was observed when combining methanol extracts of C. swynnertonii stem bark with S. glaucescens leaves against S. aureus (∑FIC 0.5), Other synergistic effects were observed against E. faecalis with dichloromethane extracts of C. swynnertonii stem bark and S. glaucescens stem bark (∑FIC 0.5), and C. swynnertonii root bark and S. glaucescens root bark (FIC index 0.3). For the remaining combinations, mainly additive effects were observed. Conclusion: Synergistic effects on bacteria were observed by combining different plant parts of S. glaucescens and C. swynnertonii suggesting that it could be beneficial to combine such extracts when used for antibacterial purposes.